2013
DOI: 10.7883/yoken.66.295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Salmonella</i> in Wild Snakes in Japan

Abstract: SUMMARY: A total of 87 wild snakes of 6 species in 2 families collected in Japan were examined for the presence of Salmonella. The prevalence of Salmonella was 58.6z, and that of Salmonella enterica subspecies I, which includes most human pathogenic serotypes, accounted for 12.6z. S. enterica subspecies I was isolated from Japanese grass snakes and Japanese four-striped snakes, and the isolates belonged to 6 serotypes: S. enterica subspecies enterica serotypes Eastbourne, Mikawashima, Narashino, Newport, Saint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
6
7
0
Order By: Relevance
“…It is in line with German study reporting unknown and rare Salmonella serovars (Krautwald-Junghanns et al 2013). The observed frequency of Salmonella carriage was higher than found in the literature (Krautwald-Junghanns et al 2013;Kuroki et al 2013) but comparable to the studies focused on captive animals (Geue and Loschner 2002;Prapasarakul et al 2012). Our results clearly confirm freeliving snakes as reservoir of numerous S. enterica subspecies and serovars (Grupka et al 2006;Krautwald-Junghanns et al 2013;Kuroki et al 2013).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It is in line with German study reporting unknown and rare Salmonella serovars (Krautwald-Junghanns et al 2013). The observed frequency of Salmonella carriage was higher than found in the literature (Krautwald-Junghanns et al 2013;Kuroki et al 2013) but comparable to the studies focused on captive animals (Geue and Loschner 2002;Prapasarakul et al 2012). Our results clearly confirm freeliving snakes as reservoir of numerous S. enterica subspecies and serovars (Grupka et al 2006;Krautwald-Junghanns et al 2013;Kuroki et al 2013).…”
Section: Discussionsupporting
confidence: 89%
“…The observed frequency of Salmonella carriage was higher than found in the literature (Krautwald-Junghanns et al 2013;Kuroki et al 2013) but comparable to the studies focused on captive animals (Geue and Loschner 2002;Prapasarakul et al 2012). Our results clearly confirm freeliving snakes as reservoir of numerous S. enterica subspecies and serovars (Grupka et al 2006;Krautwald-Junghanns et al 2013;Kuroki et al 2013). The tangible proofs for that are finding of S. enterica subspecies diarizonae 40:i:z 53 ,z 54 (not listed in White-Kauffmann-Le Minor scheme), and S. enterica subspecies diarizonae 48:k:z 57 already reported in free-living adders in Germany (Krautwald-Junghanns et al 2013) and humans in Poland (Issenhuth-Jeanjean et al 2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…None of the samples in this study were positive to Salmonella sp., otherwise very frequent finding in snakes (KUROKI et al, 2013;SCHEELINGS et al, 2011;STING et al, 2013;LUKAC et al, 2015) and a common cause of disease in humans. Low incidence of Salmonella was also described by SCHMIDT et al (2014) who reported 14.3% (8/56) Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%